Sudanese young people building capital in rural Australia: the role of mothers and community. Issue 1 (2nd January 2016) - Santoro, Ninetta; Wilkinson, Jane
Abstract : This article draws on an ethnographic study that consisted of in-depth case studies of eight Sudanese young people of refugee background living in rural Australia. Prompted by concern over deficit views of young refugees that pervade educational literature, we aimed to understand what facilitates their successful resettlement into Australian rural communities. We were particularly interested in understanding the strengths, resources and capital they draw upon and generate through their participation in out-of-school social and learning contexts, as well as within family and community networks. Here, we focus on one of the study's participants, Samir. We highlight how his mother was instrumental in providing a safe and secure home environment where significant bonding capital was generated, as well as how she facilitated her son's participation in community and ethnic networks, thus enabling him to acquire bridging and linking social capital. We conclude by discussing the implications for schools and for research.